KUALITAS PRIBADI KONSELOR: URGENSI DAN PENGEMBANGANNYA - Muskinul Fuad (Komunika, 2015)
Guidance and counseling activity is and reciprocal interaction that contain mutual-influence relation between counselor and client. Counselor have role as individual who will guide client to attain certain goal. To play this role effectively, counselor need certain capacity that define his quality. The most important capacity is counselor’s character quality (the man behind the system). Several counselors’ character quality related with counselor’s attitude, value, behavior, and spirituality. These qualities have utmost priority at counselor’s education phase. Therefore, counselor needs a character training that have psycho-spiritual-education feature